Constituent Power - Baquerizo Minuche, Jorge (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
In this paper I offer a definition of «constituent power» as a phenomenon of normative production. The objective is to carry out a task of conceptual clarification that aims to provide certain elements for a better understanding. More precisely, I will try to elucidate what type of power is captured by this concept and from what perspective it can be said that there is a relationship between constituent power and the Law.